Analysis of Critical Thinking Skills of Middle School Students on Environmental Pollution Materials - Nurhayati Nurhayati; Rudiana Agustini; Elok Sudibyo (IJORER : International Journal of Recent Educational Research, 2022)
The ability that should be possessed by students is not only limited to learning outcomes by receiving knowledge. Critical thinking skills need to be a provision to face the demands of the 21st century. Science is a subject that can not be separated from the critical thinking skills. One of the scientific materials is environmental pollution. Research has been carried out that aims to determine the students' initial critical thinking skills. The subjects used in the study were students of Junior High School Plus Nurul Hikmah. This type of research is descriptive method. The data collection instrument used a test. The results showed that the average critical thinking skillsof students was low category. The achievement of the indicator elementary clarification scored 43% in the medium category, while the indicator the basis for the decision scored 39% in the low category. The achievement of the indicator inference obtained 46% in the medium category. The indicator advances clarification scored 43% in the medium category, while the indicator supposition and integration scored 29% in the low category. In general, category for students critical thinking skills in all indicators are low. In general, criteria for students critical thinking skills in all indicators are low.